2021
DOI: 10.1007/s00264-021-05095-1
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic antropometric measurement in 3D CT for placement of two unilateral iliosacral S1 - 7.3 mm screws

Abstract: Purpose Stability of the dorsal pelvic ring is important for patient mobilisation and can be restored using several surgical procedures after fracture. Placement of percutaneous iliosacral screws is a reliable and minimal-invasive technique to achieve stabilisation of the dorsal pelvic ring by placement of two screws in the first sacral vertebra. Aim of this study was to evaluate 3D CT scans regarding the anatomical possibility to place two 7.3 mm iliosacral screws for fixation of the dorsal pelv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Suda et al [5] recently evaluated the safety of two unilateral IS S1 screws in a 3-dimensional dataset of 1,000 hemi-pelvises of 500 patients with trauma. They concluded that 99% of male and 96% of female hemi-pelvises had adequate room to place two 7.3-mm screws at a 5-mm distance into the S1 vertebra.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suda et al [5] recently evaluated the safety of two unilateral IS S1 screws in a 3-dimensional dataset of 1,000 hemi-pelvises of 500 patients with trauma. They concluded that 99% of male and 96% of female hemi-pelvises had adequate room to place two 7.3-mm screws at a 5-mm distance into the S1 vertebra.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has several advantages, particularly in patients with unstable hemodynamic conditions. However, the use of one IS screw is inferior with respect to rotational stability and load cycles [4,5]. Therefore, the fixation of two unilateral IS S1 screws or the addition of an IS S2 screw is recommended in completely unstable pelvic ring injuries [4].…”
Section: Introductionmentioning
confidence: 99%
“…Although the number of high-energy pelvic fractures is decreasing, demographic changes lead to a dramatic increase in pelvic fractures of the elderly [ 6 ]. The sacral anatomy is relatively complex and shows quite some variability [ 7 ]. Therefore, evaluation of the sacral morphology with two-dimensional methods is difficult.…”
Section: Introductionmentioning
confidence: 99%